2021
DOI: 10.1111/jnu.12685
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed‐Methods Study of Nurse Managers’ Managerial and Clinical Challenges in Mental Health Centers During the COVID‐19 Pandemic

Abstract: Purpose:The worldwide outbreak of the COVID-19 pandemic has posed challenges for nurses. The aim of this study was to examine the managerial and clinical challenges of nurse managers in mental health centers during the current COVID-19 pandemic. Design: A mixed-methods study based on an analysis of data obtained in focus groups with 25 nurse managers from two mental health centers in Israel. Methods: The quantitative phase was conducted prior to the group sessions using a structured self-administered questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(63 citation statements)
references
References 15 publications
3
56
0
4
Order By: Relevance
“…Healthcare workers learned to work in a redesigned format, were exposed to clinical challenges, acquired additional skills, and faced difficulties, all of which were accompanied by uncertainty, risk of infection, threat of morbidity, and unusual workloads (Schwarz & Bouckenooghe, 2021 ). Indeed, nurse managers in mental health centers reported on the change from a familiar routine to a new reality with family members' and volunteers' visits forbidden, and working in capsules (Kagan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare workers learned to work in a redesigned format, were exposed to clinical challenges, acquired additional skills, and faced difficulties, all of which were accompanied by uncertainty, risk of infection, threat of morbidity, and unusual workloads (Schwarz & Bouckenooghe, 2021 ). Indeed, nurse managers in mental health centers reported on the change from a familiar routine to a new reality with family members' and volunteers' visits forbidden, and working in capsules (Kagan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A different image of the job, the greater physical distance from nurse leaders and general limitations placed on interpersonal communication by the pandemic may explain these lower perceptions. This explanation is supported by Kagan et al's study ( 2021 ), which revealed that nurse leaders have felt difficulties leading and communicating to and with staff through screens during the pandemic.…”
Section: Discussionmentioning
confidence: 82%
“…Nurses are at the sharp end of the pandemic, and nurse leaders have been handling uncertainty and learning from their experiences to help manage crisis events in the future (Bergeron et al, 2006 ; Catania et al, 2021 ). In studies focusing on nursing leadership in the COVID‐19 pandemic, the importance of effective communication has been widely recognized (Catania et al, 2021 ; Digby et al, 2021 ; Kagan et al, 2021 ; Lake et al, 2021 ; Lord et al, 2021 ; Simonovich et al, 2021 ). Communication is described as nurse leaders' most vital tool and core responsibility (Lake et al, 2021 ); indeed, one study found that leadership communication is the only predictor of a nurse's willingness to care during the COVID‐19 pandemic (Lord et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to COVID‐19‐related stressors was reported to be associated with mental health problems and a decrease in self‐reported professional functioning among front‐line HCWs in Australia and China (Hendrickson et al, 2020 ; Kang et al, 2020 ). Among nursing managers in mental health centres in Israel, the professional functioning focus changed from managerial to more clinical roles (Kagan et al, 2021 ). However, there is still a gap in knowledge concerning the factors that affect the professional functioning of health care professionals during a pandemic.…”
Section: Introductionmentioning
confidence: 99%